Long-term clinical outcomes of stereotactic radiotherapy for bilateral vestibular schwannomas in neurofibromatosis type 2 patients - Puataweepong P. (2023)
Purpose: The evidence for treating patients with neurofibromatosis 2-related vestibular schwannoma (VS-NF2) using hypofractionated stereotactic radiation therapy (HSRT) is limited. This study aimed to investigate clinical outcomes in patients with VS-NF2 treated with Robotic HSRT. Methods: We retrospectively analyzed 25 NF2 patients with 48 VSs who were treated using Robotic HSRT at Ramathibodi Hospital from January 2009 to January 2020. Results: Median follow-up was 98 months (range, 24–155 months). Median tumor volume was 2.3 cm3 (range, 0.4–28.3 cm3). Median prescribed dose was 18 Gy (range, 18–25 Gy) in three fractions (range, 3–5). The 5- and 10-year local control rates were 87% and 80%, respectively. The 5- and 10-year hearing preservation rates were 59% and 35%, respectively. Three patients developed new symptoms associated with transient volume expansion after treatment: hydrocephalus in one, facial weakness in one, and ataxia in one. No patient developed worsening of trigeminal nerve function. No histologically confirmed of radiation induced malignancy was reported in the study. Conclusions: Robotic HSRT demonstrated excellent long-term tumor control with a low non-auditory complication rate in patients with VS-NF2. However, preservation of hearing remains a major concern.